2013
DOI: 10.1039/c3cp00008g
|View full text |Cite
|
Sign up to set email alerts
|

pH-Sensitive nanocargo based on smart polymer functionalized graphene oxide for site-specific drug delivery

Abstract: Graphene oxide (GO) was functionalized covalently with pH-sensitive poly(2-(diethylamino) ethyl methacrylate) (PDEA) by surface-initiated in situ atom transfer radical polymerization. The structure of the PDEA-grafted GO (GO-PDEA) were examined by Fourier-transform infrared spectroscopy, proton nuclear magnetic resonance spectroscopy, X-ray photoelectron spectroscopy, thermogravimetric analysis and atomic force microscopy. The grafted PDEA endowed the GO sheets with good solubility and stability in physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 37 publications
2
44
0
1
Order By: Relevance
“…CH and RCONH 2 were denoted in the absorption peaks of 6.868 and 7.609 ppm, respectively. All of these indicated that the major PAM functional groups are found in the spectrum . Compared to the HPAM/GO spectrum, the NH 2 and CH 2 peaks in HPAM become broader and wide indicating modification in HPAM backbone after interacting with GO sheet; however, there are existence of new peaks marks with different shapes and symbols at 6.873 ppm for ArOH and 3.639 ppm representing RCONH 2 which certainly indicated how oxygen atom in GO interact with NH 2 of HPAM to form hydrogen bond.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…CH and RCONH 2 were denoted in the absorption peaks of 6.868 and 7.609 ppm, respectively. All of these indicated that the major PAM functional groups are found in the spectrum . Compared to the HPAM/GO spectrum, the NH 2 and CH 2 peaks in HPAM become broader and wide indicating modification in HPAM backbone after interacting with GO sheet; however, there are existence of new peaks marks with different shapes and symbols at 6.873 ppm for ArOH and 3.639 ppm representing RCONH 2 which certainly indicated how oxygen atom in GO interact with NH 2 of HPAM to form hydrogen bond.…”
Section: Resultsmentioning
confidence: 94%
“…The results in Table indicate negative zeta potential for all the measured samples showing improved stability. The zeta potential of the composites shows stronger intercalation between the HPAM and GO nanosheet, indicating that improved dispersion stabilization has been achieved …”
Section: Resultsmentioning
confidence: 99%
“…118 The potential drug delivery systems are superior to free drug in a few aspects, such as longer circulation time, higher drug uptake and selectivity, lower dosage, and better therapeutic efficacy thereof. Doxorubicin (DOX, adriamycin, C 27 H 29 NO 11 ) is commonly used in chemotherapy, for example, for the treatment of Kaposi’s sarcoma, ovarian carcinoma, lung, and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The improved potency of GO‐P4VP‐CPT could be because of the better water solubility of GO‐P4VP and electrostatic attractions between the positively charged P4VP and the negatively charged cell membrane. The uptake mechanism of drug and GO‐P4VP by cells could be achieved through endocytosis, as demonstrated previously . The biocompatible GO‐P4VP exhibits increased drug efficacy and prevents degradation, thus preserving the anticancer activity of the drug.…”
Section: Resultsmentioning
confidence: 99%
“…The uptake mechanism of drug and GO-P4VP by cells could be achieved through endocytosis, as demonstrated previously. 13,15,33 The biocompatible GO-P4VP exhibits increased drug efficacy and prevents degradation, thus preserving the anticancer activity of the drug. This system has several advantages over micelles and liposome nanoparticles, such as retention of biological activity of the drug, slow and steady drug release, outstanding stability and a high loading capacity.…”
Section: Resultsmentioning
confidence: 99%